Klotho, FOXO1 and cytokines associations in patients with coronary artery disease. (May 2021) - Kazemi Fard, Toktam; Ahmadi, Reza; Akbari, Tooran; Moradi, Nariman; Fadaei, Reza; Kazemi Fard, Mohadeseh; Fallah, Soudabeh
Highlights: Klotho expression showed a significant reduction in coronary artery disease PBMCs. Klotho serum levels were decreased significantly in atherosclerotic patients. FOXO1 gene expression was increased in coronary artery disease PBMCs. Klotho was a good Biomarker for diagnosis and differentiation of CAD from controls. Abstract: Introduction: Atherosclerosis is one of the main reasons for adult mortality in advanced populations and countries with high stress levels. Klotho family are single-pass trans-membrane proteins that involve in the genesis and progression of various diseases, including acardiovascular disease, apoptosis and stress oxidative imbalance. Present study, investigates the pattern of changes in Klotho and FOXO1 gene expressions and levels in atherosclerosis. Methods: Present case control study consisted of 79 patients with atherosclerosis and 78 healthy controls. PBMC (peripheral mono-nuclear blood cells) expression levels of Klotho and FOXO1 were assayed, using qPCR method. Serum concentration of Klotho and FOXO1 were measured by ELISA method. Results: A significant reduction was found in PBMC genes expression levels of Klotho (P < 0.01) of patients as comparison with controls. PBMC Gene expression of FOXO1 in patients was increased significantly (P < 0.01) when compared with controls. Pearson analysis showed a positive correlation between PBMC Klotho gene expression and Klotho levels of patients (P < 0.01). The correlation between serum concentrations of Klotho and FOXO1 of patients was also positive significantly (P < 0.01). AUC of ROC for gene expression and serum concentration of Klotho in patients were 0.701 and 0.737 respectively. Conclusion: Investigating the PBMC gene expression and serum concentration of Klotho in patients with atherosclerosis is suggested could be a convenient novel biomarker for predicting, prognosis, monitoring the disease progression and designing a suitable drug for patients with atherosclerosis.